Improvement of aerodynamic performance of a winged compound helicopter due to single-rotor lift-offset - Sugawara, H.; Tanabe, Y. (My University, 2021)
A system of single-rotor lift-offset combined with differential flaps on the fixed wing is investigated through numerical simulations. A simplified computational model consisting of a main rotor and a winged-body is utilized. The aerodynamic performance is evaluated in high-speed cruising flight where the advance ratio is 0.7. The effect of lift-offset on overall aerodynamic performance and the influence of aerodynamic interaction on the wing are investigated for the UH-60A rotor blade and the optimized rotor blade designed at JAXA. Numerical results show that the single-rotor lift-offset combined with the differential flaps significantly improves the overall aerodynamic performance for both rotors. The lift-offset dramatically enhances the rotor performance and minimizes the reduction of the aerodynamic performance of the winged-body due to the interaction with the rotor. Different interactional effects between the rotors with the wing are observed. It is observed that highly twisted blades significantly impact the wing under the advancing side due to the aerodynamic interactions.